A new variable stiffness colonoscope makes colonoscopy easier: a randomised controlled trial. Issue 6 (1st June 2000) - Brooker, J C; Saunders, B P; Shah, S G; Williams, C B
Abstract : BACKGROUND: Colonoscopy remains technically difficult in 10–20% of procedures due to variable colonic anatomy and fixation. The ability to vary endoscope shaft flexibility may help insertion to the caecum. METHODS: Consecutive patients attending for day case colonoscopy were randomised to examination with either the conventional Olympus CF200HL (200HL) or a new variable stiffness (VS) colonoscope. Intubation time, use of stiffening function, and patient pain scores were compared. RESULTS: Of 100 cases, 43 were performed with the 200HL and 57 with the VS. Four incomplete examinations occurred with the 200HL (two sigmoid fixations, two benign strictures) and two with the VS (one obstructing cancer, one fixed sigmoid). Changing to the paediatric scope was successful in all but one patient from each group (obstructive lesions). Stiff mode was applied 23 times in 18 patients and was effective in 15 of these. Intubation time was quicker with the VS (median 6 minutes 32 seconds) than with the 200HL (median 10 minutes 35 seconds) (p=0.0005). Pain scores were less with the VS (median 7) than with the 200HL (median 24) (p=0.0081). CONCLUSIONS: The variable stiffness colonoscope combines paediatric shaft characteristics with the ability to stiffen when needed. This instrument significantly reduces intubation time and patient discomfort. Further comparisons should be made with the newest colonoscopes which are less stiff.